The role of periodontal ligament elasticity in periodontal changes - numerical simulation - Andrei Capra; Cornelia Biclesanu; Ana Maria Buruiana (Amaltea Medical Publishing House, 2022)
The clinical applications of oral mucosal biomechanics are particularly important in determining how stimulation can be performed for tissue remodeling, in understanding the level of pressure that can be applied to the painful threshold, in osseous resorption, and the availability of tissue movement. This study shows, through the finite element, the way in which the periodontal ligament behaves at the level of all dental surfaces in nonlinear model and 3 levels of alveolar bone retraction (0 %, 50%, 75%). From the point of view of geometric construction, each model consists of 3 independent components: the alveolar bone, the periodontal ligament (PL) and the tooth. The deformities on the lingual surface are very small compared to the other surfaces. The deformity increases progressively with the loss of the supporting bone. From a physiological point of view, the nonlinear model is much closer to reality because it simulates the reaction of the tissue to its immediate loading by a very low rigidity after which, due to the hydrostatic pressure created in the interstitial fluid, the value of tissue rigidity increases exponentially.